Cross-cultural adaptation and metric analysis of the Adult Difficult Intravenous Access Scale for use in Brazil - Damiana Aparecida Trindade Monteiro; Fredericus Henricus Johannes Van Loon; Júlio-Cesar de La Torre-Montero; Divanice Contim; Elucir Gir; Tanyse Galon; Guilherme Nascimento de Azevedo; Silmara Elaine Malaguti-Toffano (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: to cross-culturally adapt and analyze the metric properties of the Adult Difficult Intravenous Access Scale into Brazilian Portuguese. Method: methodological study carried out in two stages: 1) Translation of the scale from the original version in English to Brazilian Portuguese, including an assessment by a committee of nine judges, back-translation and semantic analysis; 2) Analysis of metric properties with 130 adults admitted to a hemodynamics unit in which difficult peripheral venipunctures occurred. Participants were followed up to check for the occurrence of difficult peripheral venipunctures. The instrument’s inter-rater reliability and predictive validity were analyzed. Data collection was carried out from February 2021 to April 2023 in Minas Gerais, Brazil. Results: in the assessment carried out by the committee of judges, the items presented a Content Validity Index above 0.80, after the second round of assessment. Regarding semantic analysis, professionals considered the scale relevant, easy to apply and understand. The Kappa coefficient for individual items ranged between 0.68 and 1.0. For each item scored, adult patients are three times more likely to have difficult peripheral venipuncture. Conclusion: the final version of the scale was considered clear, reliable, and easy to understand. The instrument enables a predictive score of difficult peripheral venipuncture in adults.